STRATEGIES FOR ENHANCING TEACHER COMPETENCE AND PROFESSIONALISM AT SMK PUTRA PELITA TENJOLAYA - Siti Adji; Iu Rusliana; Fikri Alamsyah; Nuraeni; Al-Gaisya, Annisa (JPG: Jurnal Pendidikan Guru, 2024)
This research is motivated by the need to understand the strategies for improving the competence and professionalism of teachers at SMK Putra Pelita Tenjolaya. Teaching is a profession characterized by a certain level of professionalism. The purpose of this study is to identify strategies for enhancing teacher competence. The research employs a qualitative research method with a descriptive approach. Data collection is conducted through semi-structured interviews. The results of this study indicate that there are several ways to enhance the professionalism and competence of teachers. These include organizing continuous training and self-development programs. Additionally, teachers can collaborate with peers to enrich insights and understanding. The role of the school principal in enhancing teacher professionalism is also crucial as a form of support for the progress of teachers at SMK Putra Pelita Tenjolaya. Keywords: Utilization; Talent; Teacher; HR; Institutions.